Insecticidal Efficacy of Metarhizium anisopliae Derived Chemical Constituents against Disease-Vector Mosquitoes - Perumal Vivekanandhan; Kannan Swathy; Amarchand Chordia Murugan; Patcharin Krutmuang (Journal of Fungi, 2022)
Insecticides can cause significant harm to both terrestrial and aquatic environments. The new insecticides derived from microbial sources are a good option with no environmental consequences. Metarhizium anisopliae (mycelia) ethyl acetate extracts were tested on larvae, pupae, and adult of Anopheles stephensi (Liston, 1901), Aedes aegypti (Meigen, 1818), and Culex quinquefasciatus (Say, 1823), as well as non-target species Eudrilus eugeniae (Kinberg, 1867) and Artemia nauplii (Linnaeus, 1758) at 24 h post treatment under laboratory condition. In bioassays, Metarhizium anisopliae extracts had remarkable toxicity on all mosquito species with LC50 values, 29.631 in Ae. aegypti, 32.578 in An. stephensi and 48.003 in Cx. quinquefasciatus disease-causing mosquitoes, in A. nauplii shows (5.33–18.33 %) mortality were produced by the M. anisopliae derived crude extract. The LC50 and LC90 values were, 620.481; 6893.990 μg/mL. No behavioral changes were observed. A low lethal effect was observed in E. eugeniae treated with the fungi metabolites shows a 14.0 % mortality. The earthworm E. eugeniae mid-gut histology revealed that M. anisopliae extracts had no more harmful effects on the epidermis, circular muscle, setae, mitochondrion, and intestinal lumen tissues than chemical pesticides. By Liquid chromatography mass spectrometry (LC-MS) analysis, camphor (25.4 %), caprolactam (20.68 %), and monobutyl phthalate (19.0 %) were identified as significant components of M. anisopliae metabolites. Fourier transform infrared (FT-IR) spectral investigations revealed the presence of carboxylic acid, amides, and phenol groups, all of which could be involved in mosquito toxicity. The M. anisopliae derived chemical constituents are effective on targeted pests, pollution-free, target-specific, and are an alternative chemical insecticide.